Makna Adverbial dalam Buku Panduan Memasak sebagai Bahan Ajar Materi Teks Prosedur Kurikulum Merdeka (SATU Press Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
This study aims to describe the meaning of adverbs in cooking guide books. Descriptive qualitative method is the method used in this study. The data source for this research is a cooking guide book entitled “Solo Traditional Culinary which is Rare”. In addition, the data of this study are procedural sentences containing adverbial meanings. Data analysis uses matching and distribution methods. The results of this study state that the cooking guide book entitled “Solo Traditional Culinary which is Rare” contains several adverbial meanings along with the amount of data found: the meaning of 'time': until (33), to (2), when (1), after (3), during (4), approximately (1), approximately (1); meaning of 'place': from (1), in (10), to (8), in (5), on (9); meaning of 'tool': with (17); the meaning of 'way': with (4); meaning of 'conditions': if (5); the meaning of 'purpose': in order to (3); the meaning of 'inclusion': while (4), along with (5); and the meaning of 'as a result': so (1). By finding some of these adverbial meanings, it can be used as teaching material for the procedural text of Kurikulum Merdeka.